ONLINE TICKET BOOKING INFORMATION SYSTEM ON CV. TAXI SIMPATI PADANGSIDIMPUAN WEB BASED - Heni Wulandari (Institute of Computer Science (IOCS), 2021)
CV. Taxi Simpati is a CV that provides transportation services in the city of Padangsidimpuan. The process of processing ticket booking data on CV. Taxi Simpati is still done manually by using handwriting. With the Online Ticket Booking Information System and computerized data processing, of course the ticket ordering process and ordering data processing will be more effective, and minimize errors in writing ticket sales reports that have been done manually. For the ticket ordering information system, it includes an input design that contains the ticket sales process. Customers login to order tickets for the desired major, system transaction automatically provide proof of ticket replacement sheets at departure.